The Reconstruction of the Bridge over the River Gère: the Engineering Work of Michael Servetus - Rodríguez Elizalde, Rubén (Journal of Ecohumanism, 2024)
Servetus was a Renaissance physician and theologian who was sentenced to death by burning at the stake for his religious opinions, following a trial that was marked by significant controversy. His work has been of significant historical importance as the first known Western thinker to propose a comprehensive understanding of the pulmonary circulation and purification processes. However, as a prominent scientist and humanist of the Renaissance, Servetus also engaged in a range of other pursuits, including geography, astrology, and civil engineering. This article, based on written testimonies, aims to examine his engineering and constructive contributions to the reconstruction of a stone bridge that collapsed due to a river flood in the city of Vienne du Dauphiné.